Anaerobic and aerobic pathways for salvage of proximal tubules from hypoxia-induced mitochondrial injury - WEINBERG, JOEL M. (2000)
We have further examined the mechanisms for a severe mitochondrial energetic deficit, deenergization, and impaired respiration in complex I that develop in kidney proximal tubules during hypoxia-reoxygenation, and their prevention and reversal by supplementation with α-ketoglutarate (α-KG) + aspartate. The abnormalities preceded the mitochondrial permeability transition and cytochrome c loss. Anaerobic metabolism of α-KG + aspartate generated ATP and maintained mitochondrial membrane potential. Other citric-acid cycle intermediates that can promote anaerobic metabolism (malate and fumarate) were also effective singly or in combination with α-KG. Succinate, the end product of these anaerobic pathways that can bypass complex I, was not protective when provided only during hypoxia. However, during reoxygenation, succinate also rescued the tubules, and its benefit, like that of α-KG + malate, persisted after the extra substrate was withdrawn. Thus proximal tubules can be salvaged from hypoxia-reoxygenation mitochondrial injury by both anaerobic metabolism of citric-acid cycle intermediates and aerobic metabolism of succinate. These results bear on the understanding of a fundamental mode of mitochondrial dysfunction during tubule injury and on strategies to prevent and reverse it.